PASAR RAKYAT SEBAGAI JEMBATAN REKONSILIASI: MEMBANGUN HUBUNGAN MASYARAKAT ANTARA WARGA EKS TIMOR-TIMUR DAN WARGA TIMOR -LESTE - Cordanis Ferreira, Alexandra; Simon H. Molan, Kristianus; Indriyati, Indriyati (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This study aims to see how the people's market of the Motaain PLBN acts as a social space that supports post-conflict reconciliation between Indonesian and Timor Leste citizens. Using a qualitative approach and Pierre Bourdieu's theory of social practice, this study analyzes four main aspects: habitus, capital, arena, and social practice. The findings show that the market is not only an economic space, but also a place where new, more open, and harmonious social relations are built. Buying and selling activities in the market bring together citizens of the two countries regularly, strengthen existing social and cultural capital, and create social practices that support a peaceful and sustainable life together.